Mix Code in the Literary Work “O Ammalek” by Goenawan Monoharto - M. Arifin Zaidin; Nunung Supratmi (Jurnal Sinestesia, 2022)
“O Ammalek” is the name of the grandmother/mother. In the book “O Ammalek” reflects on reminiscing/memorabilia for the grandmother or mother who raised the author and this moment becomes information how meaningful life means with the presence of “O Ammalek” so that anyone for a mother is very multi-meaning in a life. Code-mixing is the process of transferring linguistic units from one language to another to broaden the language’s style or variety. Code-mixing is a component of sociolinguistics that occurs not only orally but also in writing. Language is a tool that humans use to express their thoughts and feelings. Language is a means of communication that is critical in the expression of the soul. The purpose of this study is to examine the structure, function, type, and elements that contribute to the creation of code-mixing in a collection of poems by Goenawan Monoharto, entitled “O Ammalek” (2020). Qualitative descriptive method was used in this study. The primary source of data for this study is Goenawan Monoharto’s poetry collection "O Ammalek." Data were collected by researchers using documentation techniques and analyzed descriptively through data reduction, data display, and conclusion drawing. Data reduction entailed summarizing, selecting the essentials, concentrating on the critical, and deleting the irrelevant. The qualitative study employed a narrative format for the data display, while the conclusion was drawn based on the supporting evidence gathered during the research process. The results indicated that (1) There are two substantial things in O Ammalek's poetry book, namely the game of meaning and the game of sound. Wordplay in vertical typhography and phoneme play in typhoid is meaningless. “O Ammalek” is a book of poems written by Goenawan Monoharto in 2020. “O Ammalek's” poetry book contains 66 poems. 15 poems using a mixture of mangkasarak (Makassar) language. (2) employed code-mixing in the Mangkasarak language in the form of words, phrases, clauses, and idioms that served as a means of respecting an individual, confirming meaning, explaining, demonstrating self-identity, influencing a conversation, adjusting the topic/material, and expressing feelings or emotional situations, (3) code mixing in the form of words. The word "taena" indicates code mixing in the Mangkasarak language. This term translates as "no" in Indonesian, code-mixing in the form of phrases, and (4) One of the causes of code mixing is the identification of roles, identification of variations, desire to interpret, and inappropriate expressions in the language used by the speaker.